The improvement of dairy wastewater treatment efficiency by the addition of bioactivator - Sanja Posavac; Tibela Landeka Dragičević; Marijana Zanoški Hren (Mljekarstvo, 2010)
The problem in the work of dairy wastewater treatment system of milk processing industry Dukat Dairy Industry Inc., Factory Sirela, which applies the technology of activated sludge are filamentous microorganisms that cause bulking of the activated sludge and consequent inefficient treatment of wastewater. Also, this activated sludge does not have good settling properties and separation from treated water. The factors which caused such poor sludge quality are: a sudden high organic load and changes in environmental factors. In order to improve the efficiency of the system, a role and contribution of bioactivator “Aquatop® BA” was studied. The operation of the system is monitored during the period January-May in the year 2006 (bioactivator not added) and in the year 2009 (with addition of bioactivator). By adding the bioactivator better formation of flocs and good settling of activated sludge, prevention of filamentous bacteria growth and stable quality of the effluent to the required values prescribed by the Croatian waters to the chemical oxygen demand (COD) <700 mg/L and biochemical oxygen demand (BOD) <250 mg/L were achieved.